Justice Delayed in Punjab, Pakistan: A Quantitative Evidence of the Causes and Implications of Prolonged Disposal of Heinous and Serious Criminal Cases - Muhammad Shahbaz; Dr. Muhammad Iqbal Zafar* (Journal of Religion and Society, 2025)
The present study explores institutional, procedural, actor-based and case complexity issues that lead to the procrastination of serious and heinous criminal cases including murder, dacoity and grievous hurt in Punjab, Pakistan and analyzes their far-reaching social, psychological, economic and legal implications. The study involves the use of a mixed-methods approach combining both qualitative and quantitative data to provide details concerning the use of the Focus Group Discussions method in which 120 participants were interviewed in five major cities and their responses were analyzed, as well as survey data gathered through the use of a set of 600 legal professionals. According to thematic analysis, the root cause of delays is systemic inefficiencies that are old-fashioned paper-based case management, acute lack of judges and murder trial specialists, poor infrastructure, and lack of inter-agency coordination. Delays are also made worse by actor-related aspects which include frivolous adjournments by lawyers, intimidation of witnesses, strategic absconding by the accused and the demotivating judicial culture. All these are compounded by procedural bottlenecks such as ineffective summoning processes, habitual adjournments, poor use of expediting legal provisions and technological modernization. The effects of long trials are way beyond the inefficiency of the courtrooms. Delays also affect the deterioration of the popular belief in the justice system, leading the people to the informal system of resolving disputes and continuing the intergenerational feuds and polarization of the community. Both the victims and the families of the accused suffer social stigmatization and marginalization regardless of the guilt, and the financial losses burden poor litigants disproportionately perpetuating social inequality. Litigants suffer chronic stress, anxiety and learned helplessness psychologically, and criminal justice system stakeholders state that they experience compassion fatigue and emotional burnout. By law the delays erode the reliability of evidence, ruin the testimony of witnesses, make the witnesses vulnerable to become hostile for different reasons including threat, inducement, social pressures and jeopardize the capacity of prosecution to fulfill the burden of proving the case leading to acquittals that breed the culture of impunity. The results indicate a severe lack of connection between the constitutional right to a speedy trial and the reality on the ground, which demonstrates the necessity of an overall overhaul in the judicial system. Included among the recommendations are digitalization of case management, appointment of judges with specialized qualifications, strengthening of witness protection, simplifying the process, and capacity building of the institutions to revive judicial effectiveness and trust of people in the criminal justice system of Punjab. Keywords: Actor-Based Factors, Criminal Justice System, Case Disposal, Institutional Inefficiencies, Judicial Delays, Punjab, Pakistan, Socio-economic Impact.